2019
DOI: 10.1038/s41598-019-45508-1
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of EPA-rich oil impairs collagen reorganization due to elevated production of IL-10 during skin wound healing in mice

Abstract: Wound healing is an essential process for organism survival. Some fatty acids have been described as modulators of wound healing. However, the role of omega-3 fatty acids is unclear. In the present work, we investigate the effects of oral administration of eicosapentaenoic acid (EPA)-rich oil on wound healing in mice. After 4 weeks of EPA-rich oil supplementation (2 g/kg of body weight), mice had increased serum concentrations of EPA (20:5ω-3) (6-fold) and docosahexaenoic acid (DHA; 22:6ω-3) (33%) in relation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 61 publications
1
20
0
4
Order By: Relevance
“…These changes, in turn, resulted in subsequent increases in IL-10 production long in post-CPIP injuries, like those observed in the current work at 15-day post-CPIP. Although we were unable to assess macrophage phenotypes at 15-day post-CPIP due to financial constraints, our findings are in agreement with Burger et al (2019) , who observed an acceleration in the healing process following EPA supplementation for 4 weeks, with these changes in parallel with an increase in M2 macrophages and IL-10 on the 7th day after the induction of skin wounds in mice. Based on these findings, we hypothesize that omega-3 supplementation might help shift the body toward a more anti-inflammatory phenotype following the injuries that are known to trigger CRPS-I.…”
Section: Discussionsupporting
confidence: 90%
“…These changes, in turn, resulted in subsequent increases in IL-10 production long in post-CPIP injuries, like those observed in the current work at 15-day post-CPIP. Although we were unable to assess macrophage phenotypes at 15-day post-CPIP due to financial constraints, our findings are in agreement with Burger et al (2019) , who observed an acceleration in the healing process following EPA supplementation for 4 weeks, with these changes in parallel with an increase in M2 macrophages and IL-10 on the 7th day after the induction of skin wounds in mice. Based on these findings, we hypothesize that omega-3 supplementation might help shift the body toward a more anti-inflammatory phenotype following the injuries that are known to trigger CRPS-I.…”
Section: Discussionsupporting
confidence: 90%
“…Several mouse studies of experimental periodontitis induced by ligature placement for up to 2 weeks reported short‐ to long‐term post‐ligation increases in levels of pro‐inflammatory cytokines such as IL‐1β and IL‐6 and a weak increasing trend in IL‐10 48–50 . Although few studies have analyzed these cytokines in ligature‐removal repair models, Burger et al 51 examined wound healing in mouse epithelial tissue. Their study showed that levels of IL‐1β and IL‐6 protein increased in surgically wounded tissue and then decreased 1 day after injury, whereas IL‐10 levels continued to increase until day 7.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the cyclooxygenase pathway results in inhibited prostaglandins so that there is no monocyte activation mechanism to produce TNF-α and interleukin 1β, which can inhibit collagen synthesis. 9,23 The limitation in this study was the difficulty in ensuring that the whole 1ml of lemuru fish oil gel was fully absorbed in the sulcus of the periodontal ligament. Therefore, further research on the absorption capacity of lemuru oil is required, to ensure the effect of lemuru as a topical drug in the treatment of periodontitis.…”
Section: Discussionmentioning
confidence: 97%